1992
DOI: 10.1007/bf01296560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold stress on postprandial lower esophageal sphincter competence and gastroesophageal reflux in healthy subjects

Abstract: The effect of cold stress on postprandial lower esophageal sphincter competence and gastroesophageal reflux was investigated in nine healthy subjects. All subjects were studied twice in a randomized order according to a common protocol: 30 min after completion of a 700-kcal meal they put their nondominant hand in water either at 37 degrees C (control stimulus) or at 4 degrees C (stressful stimulus) cyclically for 20 min. Pulse rate and blood pressure rose significantly (P less than 0.01) during the stressful s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
2
12
1
1
Order By: Relevance
“…A previous study showed that cold stress decreases the postprandial rate of transient LES relaxations and reflux episodes in healthy humans. 13 The findings of the present study failed to demonstrate this inhibitory effect of stress on gastroesophageal reflux. Although we expected the increase of reflux episodes and gastroesophageal reflux by acute stress, gastroesophageal reflux parameters were not significantly changed by acute stress.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…A previous study showed that cold stress decreases the postprandial rate of transient LES relaxations and reflux episodes in healthy humans. 13 The findings of the present study failed to demonstrate this inhibitory effect of stress on gastroesophageal reflux. Although we expected the increase of reflux episodes and gastroesophageal reflux by acute stress, gastroesophageal reflux parameters were not significantly changed by acute stress.…”
Section: Discussioncontrasting
confidence: 87%
“…A few studies regarding the effect of stress on esophageal motility and gastroesophageal reflux have shown controversial results. [11][12][13] Diverse models to induce psychological stress have been used in healthy volunteer studies. To induce acute stress, validated dichotomous listening has been commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…Acid reflux episodes that occur during nighttime sleep periods are totally confined to periods of arousal, which may last for up to 10 s [9,23]. Stress from cold has also been shown to reduce the frequency of transient LES relaxations [24] and it has been found that, in dogs, spontaneous transient LES relaxation is completely suppressed by general anesthesia [25].…”
Section: Factors Influencing the Frequency Of Transient Les Relaxationsmentioning
confidence: 98%
“…However, while the application of psychological relaxation techniques has led to significant reductions in reported heartburn and duration of oesophageal acid exposure [7], clinical evidence for a decisive direct relationship between stress and GOR is still rather uncertain, with results reporting both an increase and decrease in GOR symptomatology during periods of stress [3,[8][9][10][11][12]. An indirect relationship between stress and GOR is also suggested.…”
Section: Introductionmentioning
confidence: 97%
“…For example, previous research has often involved very small sample sizes [11,12]. Investigators frequently used physical or purely cognitive stressors [3,8,11,12], even though more valid ones such as interview scenarios have been shown to increase oesophageal contractions [20].…”
Section: Introductionmentioning
confidence: 98%